2019
DOI: 10.1002/gps.5090
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches to studying the role of cognitive reserve in conversion from mild cognitive impairment to dementia

Abstract: Objectives The overall aim of the present study was to explore the role of cognitive reserve (CR) in the conversion from mild cognitive impairment (MCI) to dementia. We used traditional and machine learning (ML) techniques to compare converter and nonconverter participants. We also discuss the predictive value of CR proxies in relation to the ML model performance. Methods In total, 169 participants completed the longitudinal study. Participants were divided into a control group and three MCI subgroups, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The role of individual CR‐related factors in the progression from MCI to dementia has been explored in a few studies, with some inconsistent findings. One study showed that higher education or vocabulary scores may delay clinical onset of dementia in people with MCI 11 . Another three studies suggested that that later life social or cognitive activities, 12 intellectual social activities, 10 and education 13 were not associated with the conversion from MCI to dementia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of individual CR‐related factors in the progression from MCI to dementia has been explored in a few studies, with some inconsistent findings. One study showed that higher education or vocabulary scores may delay clinical onset of dementia in people with MCI 11 . Another three studies suggested that that later life social or cognitive activities, 12 intellectual social activities, 10 and education 13 were not associated with the conversion from MCI to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between individual CR‐related factors and the MCI progression to dementia were relatively weaker or not significant. In our study, to capture CR accumulated through the lifespan, we used SEM to extract the CR indicator based on life‐course (through early, middle, and late life) educational and mentally stimulating activities, and the measure was weighted according to its contribution to the score 9,11 . Thus, it is not surprise that the association of lifespan CR indicator with MCI/dementia was stronger than the association of individual CR‐enhancing factors with MCI/dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to predict who will progress to AD dementia from MCI will allow identifying the individuals who could benefit the most from clinical trials. As a result, early prediction of AD could provide the potential therapeutic windows to slow down the progression process [8].…”
Section: Introductionmentioning
confidence: 99%